Answer :

abx2 + (b2 - ac)x - bc = 0

abx2 + (b2 - ac)x - bc = 0


abx2 + b2x - acx - bc = 0


bx (ax + b) - c (ax + b) = 0 taking bx common from first two terms and –c from last two


(ax + b) (bx - c) = 0


(ax + b) = 0 or (bx - c) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses